Inspecting the Interview (De Gruyter, 2024)
Interviews are omnipresent and play a crucial role in various public discourses, from collecting research data to providing persons in the public eye a media platform. This volume assembles contributions by theoreticians and practitioners who conceptualize the interview from the perspectives of different fields in the humanities and social sciences such as linguistics, literary and cultural studies, musicology, psychology, and philosophy.